River linking : a millennium folly? - Pāṭakara, Medhā, 1954-; National Alliance of People's Movements (New Delhi, [India] : National Alliance of People's Movements, 2016)
Contributed articles with reference to Indian River Linking Project, and its environmental hazards.
Includes bibliographical references.
Keywords: River engineering -- India; Water resources development -- India; Rivers -- India; River engineering; Rivers; Water resources development; India